Seventh International Symposium "Monitoring of Mediterranean Coastal Areas. Problems and Measurement Techniques Livorno (Italy) 19-20-21 June 2018 - Fabrizio Benincasa (Proceedings e report, 2018)
The Seventh International Symposium Monitoring of Mediterranean Coastal Areas. Problems and Measurement Techniques (Livorno, Italy June 19-20-21, 2018) was organized by the CNR-IBIMET in collaboration with the City of Livorno, the LEM Foundation, the FCS Foundation and the Compagnia dei Portuali di Livorno, with the patronage by Accademia Nazionale dei Lincei, Accademia dei Georgofili, The University of Florence, the Tuscany Region and the North Tyrrhenian Sea Port System Authority. The Symposium, in which scholars from all over the Mediterranean basin participated, was an opportunity to illustrate new proposals and to promote actions to protect the Mediterranean coastal marine environment. In particular, the event was characterized by the search for technical and instrumental solutions to problems related to: energy production in the coastal area, morphology and evolution of coastlines, flora and fauna of the littoral system, management and integrated coastal protection, coastline geography, human influence on coastal landscape.